Independent Association Between Malnutrition Inflammation Score and C Reactive Protein/Albumin Ratio in Hemodialysis Patients - Tur K; Güçlü A (Dove Medical Press, 2024)
Kağan Tur,1 Aydın Güçlü2 1Ahi Evran University Faculty of Medicine, Internal Medicine Department, Kirsehir, Turkey; 2Ahi Evran University Faculty of Medicine, Nephrology Department, Kirsehir, TurkeyCorrespondence: Kağan Tur, Ahi Evran University Faculty of Medicine, Internal Medicine Department, Kirsehir, Turkey, Tel +90 5057733927, Email kaantur542@gmail.com; kagan.tur@ahievran.edu.trIntroduction: This study aimed to investigate the relationship between the Malnutrition Inflammation Score (MIS) and the C-reactive protein/albumin ratio (CAR) in patients undergoing hemodialysis (HD).Materials and Methods: Sixty-six End-Stage Renal Disease (ESRD) patients on maintenance hemodialysis were recruited for the study. Malnutrition Inflammation Score, biochemical parameters, and C-reactive protein/albumin ratio were analyzed.Results: The mean age of the participants was 56.47 ± 17.3 years. A statistically significant positive correlation was found between the CRP/albumin ratio and MIS ≥ 7 (r = 0.413, p = 0.026), CRP and MIS ≥ 7 (r = 0.388, p = 0.038) and a negative correlation between albumin and MIS (r = − 0.511, p = 0.005). Additionally, MIS was negatively correlated with hemoglobin (r = − 0.412, p = 0.026) and creatinine (r = − 0.568, p = 0.001), while a positive correlation was found between MIS and ferritin (r = 0.584, p = 0.001) for MIS ≥ 7. A multiple regression ANOVA model confirmed a significant association between CAR, CRP, albumin, and MIS (F = 6.432, p = 0.002), with significant contributions from CAR (p = 0.003), albumin (p = 0.008), and CRP (p = 0.003).Conclusion: Our study is the first to show an independent association between CAR and MIS in hemodialysis patients. The CRP/albumin ratio can serve as a valuable indicator of malnutrition in this population, providing a reliable tool for assessing nutritional status.Keywords: malnutrition inflammation score, malnutrition, CRP/albumin ratio, hemodialysis